Antiviral Defence Mechanisms during Early Mammalian Development - Felix Mueller; Jeroen Witteveldt; Sara Macias (Viruses, 2024)
The type-I interferon (IFN) response constitutes the major innate immune pathway against viruses in mammals. Despite its critical importance for antiviral defence, this pathway is inactive during early embryonic development. There seems to be an incompatibility between the IFN response and pluripotency, the ability of embryonic cells to develop into any cell type of an adult organism. Instead, pluripotent cells employ alternative ways to defend against viruses that are typically associated with safeguard mechanisms against transposable elements. The absence of an inducible IFN response in pluripotent cells and the constitutive activation of the alternative antiviral pathways have led to the hypothesis that embryonic cells are highly resistant to viruses. However, some findings challenge this interpretation. We have performed a meta-analysis that suggests that the susceptibility of pluripotent cells to viruses is directly correlated with the presence of receptors or co-receptors for viral adhesion and entry. These results challenge the current view of pluripotent cells as intrinsically resistant to infections and raise the fundamental question of why these cells have sacrificed the major antiviral defence pathway if this renders them susceptible to viruses.